2019
DOI: 10.1590/1414-431x20198441
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of Bj-PRO-7a, a proline-rich oligopeptide from Bothrops jararaca venom

Abstract: The heptapeptide Bj-PRO-7a, isolated and identified from Bothrops jararaca (Bj) venom, produces antihypertensive and other cardiovascular effects that are independent on angiotensin converting enzyme inhibition, possibly relying on cholinergic muscarinic receptors subtype 1 (M1R). However, whether Bj-PRO-7a acts upon the central nervous system and modifies behavior is yet to be determined. Therefore, the aims of this study were: i) to assess the effects of acute administration of Bj-PRO-7a upon behavior; ii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Studies have revealed that PRO-7a is an M1 mAChR agonist, which is of critical relevance given the extensive research that focused on finding such a ligand [ 24 , 57 , 58 ]. The peptide specifically activates [Ca 2+ ] I transients in CHO and neuronal P19 cells expressing the M1 mAChR subtype, which are inhibited in cells pretreated with the M1 mAChR specific antagonist pirenzepine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that PRO-7a is an M1 mAChR agonist, which is of critical relevance given the extensive research that focused on finding such a ligand [ 24 , 57 , 58 ]. The peptide specifically activates [Ca 2+ ] I transients in CHO and neuronal P19 cells expressing the M1 mAChR subtype, which are inhibited in cells pretreated with the M1 mAChR specific antagonist pirenzepine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide specifically activates [Ca 2+ ] I transients in CHO and neuronal P19 cells expressing the M1 mAChR subtype, which are inhibited in cells pretreated with the M1 mAChR specific antagonist pirenzepine [ 24 ]. The PRO-7a also improved anxiolytic and antidepressant-like actions in rats, as well as increased mobility and exploration, and these effects appear to be partially dependent on M1 mAChR activation [ 57 , 58 ]. Then, since PC12 cells express the M1 mAChR endogenously [ 59 , 60 ], we investigated the potential involvement of cholinergic receptors in PRO-7a-mediated neuroprotection via activation of M1 mAChR, using the competitive antagonist DCH [ 39 ] to suppress receptor activity in our neuroprotective assay with PRO-7a in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Methods to test behavior were performed as previously described ( 7 ). All experiments were performed in a quiet and dimly illuminated room.…”
Section: Methodsmentioning
confidence: 99%
“…This same peptide has been linked by Brazilian researchers to the normalization of endothelial dysfunction related to preeclampsia, which is a disease characterized by hypertension during pregnancy, that is, the peptide is useful as an antihypertensive in cases of preeclampsia and can be effective for new treatments against the disease [90]. Still about B. jararaca peptides rich in proline, the properties of Bj-PRO 7a were also investigated by Brazilian researchers [91]. The peptides called Bj-PROs are recognized for being inhibitors of the angiotensin-converting enzyme and having pharmacological action, which resulted in the antihypertensive drug, Captopril [92].…”
Section: Species Investigatedmentioning
confidence: 99%